2020
DOI: 10.1111/ggi.14079
|View full text |Cite
|
Sign up to set email alerts
|

Digastric muscle mass and intensity in older patients with sarcopenic dysphagia by ultrasonography

Abstract: AimThe aim of this study was to investigate digastric muscle mass and intensity between no sarcopenic dysphagia and sarcopenic dysphagia.MethodsPatients aged ≥65 years were enrolled. According to the diagnostic algorithm for sarcopenic dysphagia, the patients were divided into two groups, no sarcopenic dysphagia and sarcopenic dysphagia. Handgrip strength, gait speed, skeletal muscle mass, tongue pressure, Mini Nutritional Assessment‐Short Form and Food Intake LEVEL Scale were investigated. Digastric muscle ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Ultrasonography can also be applied for the evaluation of the digastric muscle (Figure 7). In 2020, Ogawa et al [68] investigated 45 elderly patients and reported smaller digastric muscle mass in patients with sarcopenic dysphagia vs. controls. The digastric muscle mass was identified as an independent factor for predicting sarcopenic dysphagia, with a sensitivity of 0.692 and a specificity of 0.737. skeletal muscle mass index and tongue pressure.…”
Section: Ultrasonographymentioning
confidence: 99%
“…Ultrasonography can also be applied for the evaluation of the digastric muscle (Figure 7). In 2020, Ogawa et al [68] investigated 45 elderly patients and reported smaller digastric muscle mass in patients with sarcopenic dysphagia vs. controls. The digastric muscle mass was identified as an independent factor for predicting sarcopenic dysphagia, with a sensitivity of 0.692 and a specificity of 0.737. skeletal muscle mass index and tongue pressure.…”
Section: Ultrasonographymentioning
confidence: 99%
“…Adequate assessment of sarcopenic dysphagia is critical to the development of realistic swallow rehabilitation goals. Preliminary research has demonstrated the role of ultrasound in the assessment of sarcopenic dysphagia [ 89 91 ]. Rehabilitation studies into sarcopenic dysphagia in HNC are embryonic but have demonstrated encouraging results.…”
Section: Developing Areasmentioning
confidence: 99%
“…Geniohyoid muscle mass was independently associated with maximum tongue pressure and tongue muscle mass [ 36 ]. Digastric muscle mass and intensity were independent factors for sarcopenic dysphagia [ 37 ]. Geniohyoid muscle mass was significantly associated with the severity of dysphagia after salvage surgery for head and neck cancer [ 38 ].…”
Section: Sarcopenic Dysphagiamentioning
confidence: 99%